THE EFFECT OF BIORAFIA DENSITY ON DECREASING NITRATE ON THE SAIL RIVER - Sitompul, Dorlan Rotua; Budijono, Budijono; M.Hasbi, M.Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The Sail River has been contaminated with nitrate can be reduced by using biorafia (interweaving of several raffia knot masks that are mashed with shapes resembling duster as a place to attach to microorganisms). This study aimed to determine the effect of the density of biorafia in reducing levels of nitrate contained in the water of the Sail River. The study was conducted in March-April 2019 on the Sail River. This study uses a Completely Randomized Design (CRD) with a single factor, namely biorafia. Using three treatments, namely different densities (P1 = infrequent / 50simple, P2 = moderate / 75impul and P3 = meeting / 100impul), and three replications. Sampling was carried out before and after passing biorafia on artificial trenches with a one-month interval. The results showed that biorafia was able to reduce the levels of nitrate with a decrease in average not much different. The decrease in nitrate ranges from 0.1375-0.33473 mg / L to 0.0750-0.1167 mg / L (35-44%). Biorafia can be used in reducing levels of nitrate. Keywords: Biorafia, Nitrate,raffia